СОЦІАЛЬНА РЕАБІЛІТАЦІЯ ОСІБ З ПОРУШЕННЯМ ЗОРУ - Mudryi, Yaroslav (My University, 2019)
У статті розглянуто підходи до соціальної реабілітації осіб з вадами зору, засоби корекції для таких осіб. Висвітлюються дотикові, слухові та зорові орієнтири, що дозволяють полегшити орієнтування такої людини у суспільстві, сучасні інформаційні технології: програми DAISY, Mobile Speak. Vision is one of the leading functions of the man and it provides more than 90% of information about the world. Partial or complete loss of vision causes a person some difficulties in self-care, moving, orientation, communication, training, work, etc. Modern problems of socialization of visually impaired people require their solution by creating a system of social rehabilitation work. In the social rehabilitation of a person with impaired vision we may distinguish two directions: social-living and social-environmental rehabilitation, which are conducted to provide guidance, education, adaptation in the open social environment. To do this, they use touch, hearing and visual guidance, a variety of auxiliary technical and special corrective tools, modern information technologies, such as DAISY and Mobile Speak, which help facilitate the orientation of people with visual impairment in society.
SOCIAL REHABILITATION OF PERSONS WITH VISUAL IMPAIRMENT
Keywords: : Соціальна реабілітація, людина з порушенням зору, тифлотехнічні та корекційні засоби, DAISY, Mobile Speak